Colonial Biopolitics and the Great Bengal Famine of 1943 - Mallik, Senjuti (GeoJournal, 2023)
An estimated 3 million people died due to the Bengal famine of 1943. The purpose of this article is to theorize the Bengal famine through the lens of colonial biopolitics. The colonial strategies and utilitarian principles by the British authorities exacerbated the Bengal famine. Utilizing Foucault’s concept of biopolitics, I point out how the British viewed Indian bodies discursively. To reaffirm their sense of superiority, they reduced their Indian subjects to animal-like beings’ incapable of controlling their own reproduction. In order to fulfil British goals, Indian people were forced to participate in the war effort. This paper situates the local and global politics of the famine as they were wrapped up in the geopolitics of World War II, during which the British colonial authorities were far more concerned about a Japanese invasion of South Asia than they were with the lives of people dying of hunger. The article highlights how the implementation of racist policies worsened the famine since it was a product of wartime priorities and calculations. I argue that the Bengal famine of 1943 is a historic tragedy of the colonial past, which was transformed into a socially constructed catastrophe by the British colonizers.Geographers have never studied the Bengal famine of 1943, and one of the principal purposes of this paper is to fill this void.